2009
DOI: 10.1080/15504280903035761
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization and Resilience in Adolescent Children of Lesbian Mothers

Abstract: This paper reviews the historical and cultural milieu in which lesbians formed families in the late twentieth century, the psychosocial development of children of lesbian mothers, and the influence of factors that protect them from the negative influences of homophobia. It argues that the focus of research in lesbian families

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…16 During adolescence, peer relations become more important as teenagers develop a sense of identity, a deeper appreciation of interindividual difference, and a keener awareness of minority status. 19,[29][30][31] Teenage children may be more reflective about their earlier experiences of stigmatization, 15,19,27,29,[32][33][34][35] yet relatively little has been reported about the psychological well-being of adolescents who have been raised in lesbian families since birth. Studies on the teenage offspring of lesbians are largely based on data gathered in the 1990s, in which the majority of teenagers studied were conceived in heterosexual relationships before their mothers divorced and came out as lesbian.…”
mentioning
confidence: 99%
“…16 During adolescence, peer relations become more important as teenagers develop a sense of identity, a deeper appreciation of interindividual difference, and a keener awareness of minority status. 19,[29][30][31] Teenage children may be more reflective about their earlier experiences of stigmatization, 15,19,27,29,[32][33][34][35] yet relatively little has been reported about the psychological well-being of adolescents who have been raised in lesbian families since birth. Studies on the teenage offspring of lesbians are largely based on data gathered in the 1990s, in which the majority of teenagers studied were conceived in heterosexual relationships before their mothers divorced and came out as lesbian.…”
mentioning
confidence: 99%
“…GLBTQ stigma has a negative effect on the mental health and well-being of GLBTQ people (Meyer, 2003). Furthermore, among children with lesbian mothers, community-based stigma has been linked to lower self-esteem (Bos & Van Balen, 2008;Gartrell, Deck, Rodas, Peyser, & Banks, 2005;Gershon, Tschann, & Jemerin, 1999;Van Gelderen, Gartrell, Bos, & Hermanns, 2009) and feelings of anger and sadness (Gartrell et al, 2005). Although GLBTQ family members may experience stigma in any social environment, nonmetropolitan communities pose unique challenges that warrant our attention (e.g., available community resources, geography).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Although GLBTQ family members may experience stigma in any social environment, nonmetropolitan communities pose unique challenges that warrant our attention (e.g., available community resources, geography). Communitylevel factors that have been found to reduce the effects of stigma experienced by children with lesbian mothers include attending a school that incorporates GLBTQ curriculum, having a mother involved in the lesbian community, and having contact with other children with GLBTQ parents (Van Gelderen et al, 2009). However, this research did not focus on nonmetropolitan populations; thus, there is a limited understanding of what or how protective factors operate in these communities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In addition to the civic benefits, promoting LGBT organizations and the visibility of LGBT people can strengthen local families. Previous research has found that children with lesbian mothers have greater well‐being when they are connected to other children with lesbian mothers (Bos, Gartrell, Peyser, & van Balen, 2008) and when their mothers are connected to other lesbians (van Gelderen, Gartrell, Bos, & Hermanns, 2009). Community infrastructure could be developed to facilitate these connections (see Mancini, Bowen, & Martin, 2005).…”
Section: Discussionmentioning
confidence: 99%